Determinants Of Basic Immunization Completeness In The Work Area Of Enrekang City Community Health Center - Azhura, Ulan Noor; Raodhah, Sitti; Jayadi, Yusma Indah; Rahmah, Nur (Public Health Science & Religion, 2024)
Background: According to the World Health Organization (WHO) Complete immunization is a condition where a child has received complete routine immunization starting from IDL at the age of 0-11 months. The coverage of basic immunization in Indonesia still has not reached the target of the Ministry of Health's Strategic Plan for 2020. Basic immunization for infants in South Sulawesi Province is 54.2%, this also has not reached the target of the Strategic Plan for 2020. This study aims to look at the determinants of the completeness of basic immunization in work areas Health Center in Enrekang Regency City in 2022. Methods: The type of research used is quantitative with a cross sectional study design. The population in this study were all mothers who had babies who had reached the age of 12 months who lived around the work area of the City Health Center in Enrekang Regency with a total sample of 168 mothers. The sampling technique used is simple random sampling. Results: this study indicate that there is a relationship between mother's trust/belief, affordability of health facilities and the role of health workers on the determinants of basic immunization completeness in the work area of the Public Health Center in Enrekang City with a P value <0.05. Meanwhile, the variable mother's knowledge and mother's attitude did not have a significant relationship with the completeness of basic immunization, namely the p value> 0.05 using bivariate analysis chi-square test. Conclusion: Immunization coverage can be increased through counseling related to post-immunization follow-up events (KIPI) for parents and vaccine halalness and the need for updating the immunization coverage program at the Enrekang District Health Office.